The "old" and the "new": events and placemaking in Luang Prabang, Laos. Issue 1 (6th March 2017) - Staiff, Russell; Bushell, Robyn
Abstract : Purpose: The purpose of this paper is to explore Lai Heua Fai, Festival of Light, as a place making ritual in the world heritage town of Luang Prabang, a former royal capital of the Lao-speaking kingdom. It compares this centuries-old traditional festival with a very new place making festival, the Luang Prabang Film Festival which began only six years ago. Design/methodology/approach: Sense of place theorization has developed considerably in recent decades as a number of discourses have co-mingled and as social and cultural research has embraced space/place as a crucial component of knowledge production. The study explores place making in a globalized, post-modern and post-colonial world. Fieldwork was undertaken in Luang Prabang between 2008 and 2016 including interviews, observations, photographic recording and participation, leading up to the 2013 celebration of Lai Heua Fai and the 2015 film festival. Findings: Lai Heua Fai and the Luang Prabang Film Festival are spatial practices that represent the places they evoke. Both these events connect the past, the present and the future in place. The authors argue that separating "events" from "place" sets up a dichotomy that is problematic and unsustainable on many levels: perceptually, as a lived experience, epistemologically and analytically. Originality/value: The authors suggest that these two identity forming events, in the life of Luang Prabang, herald "place" and "place making" as ongoing dynamic processes of construction and re-construction where the "traditional" and the "contemporary" are constantly re-constituted as markers, in the case of this research, of Luang Prabangan identity and place attachment.